Covid-19 school closures in low- and middle-income countries: Emergent perspectives on the role of educational technology - Jordan, Katy (Journal of Learning for Development, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:2BDLYTUP 2339240:DFHS5PI3 2339240:JTUAX3R7 2339240:V7VSHKVT 2405685:AVYK5T2I 2405685:BVFLF8QP 2405685:J7AK3RMI 2405685:JV429XI7
Keywords: COVID-19; ___working_potential_duplicate; digital divide; education in emergencies. education systems; educational technology; ⛔ No DOI found

Is there Learning Continuity during the COVID-19 Pandemic? A Synthesis of the Emerging Evidence - McBurnie, Chris; Adam, Taskeen; Kaye, Tom (Journal of Learning for Development, 2020)
Since the onset of COVID-19, governments have launched technology-supported education interventions to ensure children learn. This paper offers a narrative synthesis of emerging evidence on technology-based education to understand the current experiences of learners, teachers and families. Studies find that few students in low- and middle-income countries have access to technology-supported learning with the most marginalised children appearing to have the least educational opportunities. As such, the education response to COVID-19 could widen existing inequalities.
KerkoCite.ItemAlsoKnownAs: 2405685:WFEBLP79
Keywords: dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No DOI found

The relationship between educational television and mathematics capability in Tanzania - Watson, Joseph; Hennessy, Sara; Vignoles, Anna (British Journal of Educational Technology, 2020)
Previous studies have frequently demonstrated that educational television viewing can have a positive effect on learning in low-income country contexts when shows are delivered in controlled settings. However, the consequence of day-to-day viewing in such contexts has scarcely been considered. Additionally, no recent published research has provided any information on the costs of educational television. The lack of research in these areas is striking. Examining educational television viewing in monitored settings provides limited information on the influence of routine television consumption. Further, the broad reach of numerous educational television programmes should provide low perviewer costs and, resultantly, strong cost-effectiveness findings. This PhD study therefore examined (1) the association between educational television exposure and mathematics capability and (2) the cost effectiveness of educational television interventions. To achieve this, research was carried out that centred on Ubongo Kids – a popular Tanzanian-produced show delivering mathematics-focused content.
KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13047 10.17863/cam.54714 2339240:6LGJJU8F 2339240:MVL3KA6H 2339240:U3SHRB68 2339240:XZDCXAZ7 2405685:8WKWEBZZ 2405685:A5XKUF3W 2405685:CHDUKI36 2405685:VJ8U5IDE 2405685:YENK6ASB
Keywords: Tanzania; ___working_potential_duplicate; cost effectiveness; educational television; mathematics; ⛔ No DOI found